Search for B c + → π + μ + μ - decays and measurement of the branching fraction ratio B ( B c + → ψ ( 2 S ) π + ) / B ( B c + → J / ψ π + ) - Aaij, R; Abdelmotteleb, A; Beteta, CA; Abudinén, F; Ackernley, T; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; Akar, S; et al. (SpringerOpen, 2024)
The first search for nonresonant Bc+→π+μ+μ- decays is reported. The analysis uses proton–proton collision data collected with the LHCb detector between 2011 and 2018, corresponding to an integrated luminosity of 9fb-1. No evidence for an excess of signal events over background is observed and an upper limit is set on the branching fraction ratio B(Bc+→π+μ+μ-)/B(Bc+→J/ψπ+)<2.1×10-4 at 90% confidence level. Additionally, an updated measurement of the ratio of the Bc+→ψ(2S)π+ and Bc+→J/ψπ+ branching fractions is reported. The ratio B(Bc+→ψ(2S)π+)/B(Bc+→J/ψπ+) is measured to be 0.254±0.018±0.003±0.005, where the first uncertainty is statistical, the second systematic, and the third is due to the uncertainties on the branching fractions of the leptonic J/ψ and ψ(2S) decays. This measurement is the most precise to date and is consistent with previous LHCb results.